A scalable group-rekeying scheme using secret mask patterns. (3rd April 2006) - Asem, Yaser M.; Kara, A.
In this paper, we propose a new group-rekeying method for changing the multicast group key matrix-mask-based group-rekeying (MMGR). The main aim of our rekeying method is to solve the rekeying problem that arises when some group members leave the group. In MMGR, the group controller constructs the rekeying message using a numerical matrix, and the group members apply secret bit masks on the matrix to get the group key. MMGR does not need computationally expensive encryption of the group key before transmission and hence eliminates the need to decrypt it after receiving the rekeying message. In MMGR, rekeying message construction and group key retrieval processes need only simple operations. The computational cost of the rekeying server is low, and the computational cost of the group members is low and constant regardless of the rekeying message size.